Reinventing the Methodology of Studying Contemporary China : Re-testing the One-dot Theory - YU, Peter Kien-hong (Springer Singapore : Imprint: Springer, 2017)
This book illustrates how the one-dot theory, which is a dialectical study, is well suited to describing, explaining and inferring contemporary China's past, present and future. It argues that since October 1949, the field of contemporary China studies has been dominated by modified and abandoned non-dialectical theories and models. It also challenges selected non-dialectical theories and models which were first generated in the West, such as the game theory and rational (choice) theory. With its emphasis on methodology, the book offers a valuable resource for academics, researchers and practitioners alike with an interest in logically, systematically and coherently unraveling Taiwan's and mainland China's contemporary politics and international relations.
Keywords: Social sciences.; Ethnology -- Asia.; China -- History.; Asia -- Politics and government.; Sociology -- Research.; elektronické knihy; electronic books